Diana Umbronensis a Scoglietto : santuario, territorio e cultura material (200a.C.-550d.C.) - Sebastiani, Alessandro,; Chirico, Elena,; Colombini, Matteo,; Cygielman, Mario, (Archaeopress Roman archaeology ;, 2015)
This volume details the archaeological investigations of the ager Rusellanus, in coastal southern Etruria, undertaken by the Alberese Archaeological Project. It focuses on the Roman temple and sanctuary dedicated to Diana Umbronensis, located at Scoglietto (Alberese - GR) on the ancient Tyrrhenian coast.